The optimization of the ZSM-5 catalyst activity with respect to crystallinity - Modutwane, Angel Tumelo (Department of Chemical Engineering, 2014)
In the synthesis of zeolites optimization of factors such as crystallinity, which encapsulates morphology, and acidity can result in optimal activity. Optimal activity is vital in chemical industries due to the fact that it results in higher yields, better selectivities and lower operational costs. In this project the effect of crystallinity on activity is investigated to get a better understanding of performance in terms of activity of amorphous, partially crystalline and highly crystalline materials using isomerisation of para-xylene as the probe reaction.